Correlation Analysis of Knowledge Creation with Motivation of Coursera Platform Users Based on SECI-Nonaka Model - Romadhan, Nurul Habib; Novelawaty, Yeni Dwi; Ashshiddiqi, Muhammad Hanif; Nardanti, Ayudya Tri; Prabowo, Boby (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: In the digital era, online learning has become one of the main alternatives in acquiring new knowledge and skills. One of the most widely used platforms is Coursera, which provides various courses from world-renowned universities and institutions. The success of learning on this platform depends not only on the quality of the materials provided, but also on how users create and develop their own knowledge during the learning process. This SECI model explains how individuals and organizations transform tacit (implicit) knowledge into explicit, and how this process can enhance understanding and innovation in a learning environment.Objective: This study aims to analyze the correlation between knowledge creation based on the SECI-Nonaka Model and the motivation of Coursera platform users.Methods: The research model used in this study is quantitative with a symmetrical associative approach. This research was conducted to see the relationship between variables X and Y used a survey method conducted online. The population in this study were users of the Coursera platform, and the research sample totaled 28 people. This research focuses on how the knowledge creation process based on the SECI model (Socialization, Externalization, Combination, Internalization) has a correlation with user motivation in using the Coursera online learning platform.Results: The results showed that H1 was accepted with a significance value of 0.000 which was < 0.05 with a correlation coefficient value of 0.650 with a strong correlation strength. H2 is accepted with a significance value of 0.001 which is < 0.05 with a correlation coefficient value of 0.588 with a strong correlation strength. H3 is accepted with a significance value of 0.003 which is < 0.05 with a correlation coefficient value of 0.538 with a strong correlation strength. H4 is accepted with a significance value of 0.000 which is < 0.05 with a correlation coefficient value of 0.787 with a very strong correlation strength.Conclusion: The four hypotheses proposed in this study are accepted that the SECI model has a positive relationship with Coursera user motivation. With users motivated to learn on the Coursera platform, the knowledge creation process will be created. Thus, it can be stated that the Coursera learning platform is a supporting platform for knowledge creation, where knowledge creation is one form of knowledge management.